COMPARATIVE ANALYSIS OF OUTSOURCING REGULATION IN INDONESIA AND THE PHILIPPINES - Liawati, Mira Sonia Seba; Saragi, Paltiada; Panjaitan, Hulman (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This study examines the Comparative Analysis of Outsourcing Legal Regulations in Indonesia and the Philippines. Unlike Indonesia, which absolves the Employer Company of responsibility for fulfilling the rights of outsourced workers, the focus of outsourcing regulations in the Philippines—from the Labor Code to Department Order No. 174 Series of 2017—is the protection of outsourced workers' rights. The guaranteed protection of outsourced workers’ rights has proven successful as a foundation for the Philippines to foster a healthy outsourcing climate, which has become one of the catalysts for economic development in the Philippines, evenduring the pandemic. This study is a normative juridical research conducted through legal comparison using a Statute Approach and a Comparative Approach. The legal materials utilized in this research consist of primary, secondary, and tertiary legal sources. Data collection was conducted through document studies from 2023 to 2024. Based on the collected data, this study employs a qualitative approach for data analysis. In Indonesia, outsourcing is regulated by Law No. 13 of 2003 on Manpower, Law No. 6 of 2023 on Job Creation, and their implementing regulations. Meanwhile, the Philippines regulates outsourcing through DOLE 174, Republic Act No. 11199 of 2019 and its amendments, as well as related rules that emphasize the welfare protection of outsourced workers and legal certainty for investors. Worker protection in the Philippines focuses more on workers' fundamental rights and occupational safety, with policies requiring outsourcing companies to ensure their workers receive protection aligned with national standards.